Q. 23.6( 8 Votes )

If A = {a, b, c,

Answer :

(i) B - C represents all elements in B that are not in C


B - C = {a, c}


A(B - C) = {a, c}


AB = {a, c, e}


AC = {b, e}


(AB) - (AC) = {a, c}


A(B - C) = (AB) - (AC)


Hence proved


(ii) BC = {e, g}


A - (BC) = {a, b, c, d}


(A - B) = {b, d}


(A - C) = {a, c, d}


(A - B) (A - C) = {a, b, c, d}


A - (BC) = (A - B) (A - C)


Hence proved


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Mark the correct RD Sharma - Mathematics

Mark the correct RD Sharma - Mathematics

If A and B are twRD Sharma - Mathematics

If A and B are twRD Sharma - Mathematics

A survey shows thRD Sharma - Mathematics

If A = {x : x <spRS Aggarwal - Mathematics

Mark the correct RD Sharma - Mathematics

In a group of 70 RD Sharma - Mathematics

If P and Q are twRD Sharma - Mathematics